Literature Review on the Use of Interactive Labs Technology in The Context of Science Education - Ni Nyoman Sri Putu Verawati; Agus Abhi Purwoko (International Journal of Ethnoscience and Technology in Education, 2024)
Science education is a cornerstone in preparing students for the complexities of the contemporary world. In this vein, the integration of Interactive Labs technology resources into science learning presents a promising avenue. This literature review delves into the expansive realm of Interactive Labs within science education, shedding light on their myriad advantages and burgeoning trends. Employing the "Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA)" methodology, the review meticulously scrutinizes pertinent articles, elucidating the transformative potential inherent in Interactive Labs, virtual reality (VR), and augmented reality (AR) technologies in the realm of science education. One of the primary revelations of this review is the manifold benefits that Interactive Labs offer. These technologies not only enhance students' attitudes towards science but also bolster their academic performance, foster critical thinking skills, and augment engagement levels. Furthermore, Interactive Labs present a cost-effective, scalable, and safe alternative to traditional laboratory settings, thereby democratizing access to hands-on scientific experimentation. Particularly noteworthy are the transformative capabilities of VR and AR technologies within the educational landscape. By immersing students in simulated environments, VR and AR facilitate experiential learning, allowing students to interact with scientific concepts in ways previously unimaginable. This immersive approach not only enhances comprehension but also kindles a sense of wonder and curiosity, vital for nurturing a lifelong passion for science. In conclusion, this literature review underscores the pivotal role that technology plays in shaping the future of science education. By equipping educators and institutions with innovative tools, such as Interactive Labs, VR, and AR, it paves the way for enriched learning experiences and contributes to the continual evolution of science education. The integration of technology promises to be instrumental in realizing the full potential of science education, thereby fostering a generation of adept and inspired scientific minds.